Wujud Rahmatan Lil Alamin Dalam Kehidupan Berbangsa Dan Bernegara - Aulia Khoirunni aa’ Qosiimah; Renaya Felisha; Erika Ananda; Wismanto Wismanto; Ilham Hudi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
.Islam Rahmatan Lil Alamin is the goal of Islam as a whole (Maqashid Am Li Syariah). All Islamic teachings bring benefit, mercy and peace to the world, to living creatures and to all mankind. The aim of this research is to reveal the main characteristics and objectives of Islamic teachings rahmatan lil alamin in the social and cultural life of modern humans. The method used in this research is the literature review method, namely analyzing scientific literature related to Islam Rahmatan Lir Al-Alamin from a socio-cultural perspective. The results of this research are that the implementation of Rahmatan Lil Alamin's values in social life can be seen in school education, society, places of worship and workplaces, as well as in the mass media. The implementation of Rahmatan Lilalamin's values in cultural life can be seen in the development of science, language, ideology and customs.